Sponge Diversity in Kinamang Beach Area Malalayang District Manado City - Musak, Putra; Sumilat, Deiske Adeliene; Schaduw, Joshian Nicolas William; Rumengan, Antonius Petrus; Angkouw , Esther Dellayani; Undap , Suzanne Lydia (Sam Ratulangi University, 2023)
Spons are primitive living settled animals that are filter feeders. These animals are commonly found in tropical and subtropical waters, ranging from the intertidal zone to the subtidal. The aim of this study is to know the diversity of species and the content of bioactive sponges. Sponge data collection: ecological index, species composition, and density of sponge as well as knowledge of the study of bioactive sponge using the library study of the research carried out and using the scientific article of the last 10 years, from 2013 to 2023. The study used the transect belt method that has been modified. From the use of the method, 17 Families were obtained, 48 individuals at a depth of 7 m and 118 individuals at 14 m. Based on the results of this study showed that the index of diversity obtained from the analysis results belonged to the average in 7 m and 14 m. Distribution patterns obtained from data analysis results obtain the distribution pattern at a depth of 7 m grouping 5 families, uniform 5 families, and random 1 family. At a depth of 14 m, the most spread pattern is the uniform spread of 10 families, and the spread model groups 4 families. The index of diversity obtained from the results of data analysis is high (stable). The composition of the species obtained from the results of the analysis showed the highest species of sponges at a depth of 7 m was 33.33%, the highest species at a deep of 14 m is 33.90%, and the composition type of the lowest sponge depth 7 m is 0%, the lower species on a deep 14 m was 11.86%. The highest value of spongy density at a depth of 7 meters is 2.44 ind/m² and the lowest is 0.15 ind/m², whereas, at depths of 14 meters, the highest values are 3.16 ind/m² and lower is 0.08 ind/m² and a library study of the bioactive content received 27 articles related to the family obtaining at the research site and in teluk manado. Keywords: Diversity, Sponge, Kinamang Beach, Bioactive Content Abstrak Spons merupakan hewan primitif yang hidup menetap yang bersifat filter feeder (menyaring). Hewan ini sangat umum dijumpai di perairan tropis dan sub tropis, sebarannya mulai dari zona intertidal hingga zona subtidal. Tujuan dari penelitian ini yaitu mengetahui keanekaragaman jenis dan kandungan bioaktif spons. Pengambilan data spons : indeks ekologi, komposisi jenis dan kepadatan spons serta mengetahui kajian mengenai bioaktif spons dengan menggunakan studi pustaka dari penelitian yang telah dilakukan dan menggunakan artikel ilmiah 10 tahun terakhir tahun 2013 sampai 2023. Penelitian ini menggunakan metode belt transek yang telah dimodifikasi. Dari pengunaan metode tersebut diperoleh 17 Famili, 48 individu pada kedalaman 7 m dan 118 individu pada kedalaman 14 m. Berdasarkan hasil dari penelitian ini menunjukkan bahwa indeks keanekaragaman yang diperoleh dari hasil analisis tergolong sedang pada kedalam 7 m dan 14 m. Pola Sebaran yang diperoleh dari hasil analisis data didapatkan pola sebaran pada kedalaman 7 m pola sebaran mengelompok 5 famili, pola sebaran seragam 5 famili,dan pola sebaran acak 1 famili. Sedangkan pada kedalaman 14 m pola sebaran terbanyak yaitu, pola sebaran seragam 10 famili, dan pola sebaran mengelompok 4 famili. Indeks keseragaman yang diperoleh dari hasil analisis data yaitu tergolong tinggi (stabil). Komposisi jenis yang diperoleh dari hasil analisis menunjukkan jenis spons tertinggi pada kedalaman 7 m yaitu 33,33 %, jenis spons tertinggi pada kedalaman 14 m yaitu 33,90 %, dan komposisi jenis spons terendah kedalaman 7 m yaitu 0 %,jenis spons terendah pada kedalaman 14 m yaitu 11,86 %. Nilai kepadatan spons tertinggi pada kedalaman 7 m yaitu 2,44 ind/m² dan terendah yaitu 0,15 ind/m², sedangkan pada kedalaman 14 meter dengan nilai tertinggi yaitu 3,16 ind/m² dan terendah yaitu 0,08 ind/m² dan studi pustaka mengenai kandungan bioaktif yang didapatkan 27 artikel yang berkaitan dengan famili yang didapatkan di lokasi penelitian dan di teluk manado. Kata Kunci: Keanekaragaman, Spons, Pantai Kinamang, Kandungan Bioaktif